The biology of Giardia spp. - Adam, R D (1991)
Gardia spp. are flagellated protozoans that parasitize the small intestines of mammals, birds, reptiles, and amphibians. The infectious cysts begin excysting in the acidic environment of the stomach and become trophozoites (the vegetative form). The trophozoites attach to the intestinal mucosa through the suction generated by a ventral disk and cause diarrhea and malabsorption by mechanisms that are not well understood. Giardia spp. have a number of unique features, including a predominantly anaerobic metabolism, complete dependence on salvage of exogenous nucleotides, a limited ability to synthesize and degrade carbohydrates and lipids, and two nuclei that are equal by all criteria that have been tested. The small size and unique sequence of G. lamblia rRNA molecules have led to the proposal that Giardia is the most primitive eukaryotic organism. Three Giardia spp. have been identified by light lamblia, G. muris, and G. agilis, but electron microscopy has allowed further species to be described within the G. lamblia group, some of which have been substantiated by differences in the rDNA. Animal models and human infections have led to the conclusion that intestinal infection is controlled primarily through the humoral immune system (T-cell dependent in the mouse model). A major immunogenic cysteine-rich surface antigen is able to vary in vitro and in vivo in the course of an infection and may provide a means of evading the host immune response or perhaps a means of adapting to different intestinal environments.